KEEFEKTIFAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN SOFTWARE ARTICULATE STRORYLINE PADA MATA PELAJARAN BAHASA INDONESIA - Sriyanti Situti Noor; Pattaufi Pattaufi; Abdul Haling; Nurhikmah H Nurhikmah H (Phinisi Integration Review, 2023)
This study aims to develop and validate products in the form of interactive learning media using the Indonesian language subject articulate storyline software. The method used in this research is Research and Development (R&D) with the stages of developing the ADDIE model (Analysis, Design, Development, Implementation and Evaluation), the research is carried out up to the evaluation stage. the average value of material experts is 3.5 which is categorized as "very feasible", for validation media experts obtain an average value of 3.75 which is categorized as "very feasible". The results of the assessment on the trials conducted by students obtained an average score of 3.8 in the “very practical” category, and the response of Indonesian language teachers included an average of 3.8 “very practical”.Penelitian ini bertujuan untuk mengembangkan dan memvalidasi produk berupa media pembelajaran interaktif menggunakan software articulate storyline mata pelajaran Bahasa Indonesia. Metode yang dipakai pada penelitian adalah Research and Development (R&D) dengan tahapan pengembangan model ADDIE (Analysis, Design, Development, Implementation dan Evaluation), penelitian dilaksanakan hingga tahap evaluation. rata-rata nilai dari ahli materi sebesar 3,5 yang dikategorikan "sangat layak", untuk validasi ahli media memperoleh nilai rata-rata sebesar 3,75 yang memperoleh kategori "sangat layak". Hasil penilaian pada uji coba yang dilakukan peserta didik memperoleh nilai rata-rata 3,8 dengan kategori “sangat praktis”, serta respon guru mata pelajaran Bahasa Indonesia mencakup rata-rata 3,8 “sangat praktis”.